Unveiling the Merdeka Curriculum in Indonesia: Insights from Educators and Policymakers on Its Effectiveness and Implications - Allegra Kartika (Pusat Publikasi Nusantara, 2024)
This study examines the Merdeka Curriculum, a recent educational reform in Indonesia designed to empower teachers and students with greater flexibility in learning. Rooted in the philosophy of